1999
DOI: 10.1073/pnas.96.9.5268
|View full text |Cite
|
Sign up to set email alerts
|

A neuronal morphologic type unique to humans and great apes

Abstract: We report the existence and distribution of an unusual type of projection neuron, a large, spindle-shaped cell, in layer Vb of the anterior cingulate cortex of pongids and hominids. These spindle cells were not observed in any other primate species or any other mammalian taxa, and their volume was correlated with brain volume residuals, a measure of encephalization in higher primates. These observations are of particular interest when considering primate neocortical evolution, as they reveal possible adaptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
349
3
7

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 455 publications
(378 citation statements)
references
References 52 publications
19
349
3
7
Order By: Relevance
“…SAI appears to correspond to Rose's (1928) granular insular areas (i7, i8, and i9). The cytoarchitecture of area LA and the location of the VENs in this area of anterior cingulate cortex are illustrated in von Economo (2009) and Nimchinsky et al (1995Nimchinsky et al ( , 1999.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SAI appears to correspond to Rose's (1928) granular insular areas (i7, i8, and i9). The cytoarchitecture of area LA and the location of the VENs in this area of anterior cingulate cortex are illustrated in von Economo (2009) and Nimchinsky et al (1995Nimchinsky et al ( , 1999.…”
Section: Resultsmentioning
confidence: 99%
“…In a comparative study of the distribution of the VENs in LA in primates, Nimchinsky et al (1999) found them to be present in all the great apes (chimpanzees, bonobos, gorillas, and orangutans), but not in any other non-human primates. In this study, the VENs declined in abundance with increasing phylogenetic distance from humans, with bonobos and chimpanzees having more than gorillas, which in turn had more than orangutans, which had only a few isolated VENs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be that the cingulate response reflects neural synchronization [55] or synaptic events, detectable through EEG or fMRI (the techniques usually applied in humans), but not evident at the level of single-unit spike trains (as collected from monkeys). Furthermore, there are cytoarchitectonic differences between human and monkey ACC [56], which make it plausible that functional differences also exist.…”
Section: Localization Of the Conflict Responsementioning
confidence: 99%
“…In this context, one may guess that a certain degree of depressiveness may be of evolutionary advantage. Interestingly, some of the involved brain regions may represent specific emotion expectation processing in humans as parts of the ventromedial thalamus were found to be more prominent in humans compared to lower primates, and certain cytological features in anterior insula and ACC were found only in humans but not in primates (Nimchinsky et al, 1999;Craig, 2002).…”
Section: Anatomical and Functional Features Of The Revealed Areasmentioning
confidence: 99%